2010
DOI: 10.1007/s00216-010-3584-0
|View full text |Cite
|
Sign up to set email alerts
|

Headspace solid-phase microextraction followed by gas chromatography tandem mass spectrometry for the sensitive determination of benzotriazole UV stabilizers in water samples

Abstract: A sensitive procedure for the determination of five ultraviolet (UV) absorbers, belonging to the benzotriazole class, in environmental water samples is proposed. Analytes were first extracted and concentrated from the matrix and then selectively determined by gas chromatography in combination with tandem mass spectrometry detection. The high lipophilic character of some of the investigated species resulted in a strong trend to remain sorbed on solid surfaces, even after addition of considerable percentages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…Recent study (Carpinteiro et al, 2010) reported that concentrations of UV-P, -326, and -328, in raw wastewater samples ranged from 5 ± 2 to 16 ± 1, from 3.5 ± 0.5 to 57 ± 9, and from 1.0 ± 0.1 to 19 ± 2 ng/l, respectively. The results of the above survey show that, BUVSs residues exist in very low concentrations; which were mostly below detection limits and the detected levels in the Nakata et al, (2009).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent study (Carpinteiro et al, 2010) reported that concentrations of UV-P, -326, and -328, in raw wastewater samples ranged from 5 ± 2 to 16 ± 1, from 3.5 ± 0.5 to 57 ± 9, and from 1.0 ± 0.1 to 19 ± 2 ng/l, respectively. The results of the above survey show that, BUVSs residues exist in very low concentrations; which were mostly below detection limits and the detected levels in the Nakata et al, (2009).…”
Section: Resultsmentioning
confidence: 98%
“…BUVSs enter aquatic environments either directly, via wash-off from skin and clothes during water recreational activities, or indirectly, via discharges of sewage and swimming pool waters. As a result, BUVSs have been detected in environmental and biological matrices such as water, soil, sediment and organisms (Nakata et al, 2009;Carpinteiro et al, 2010). Furthermore, Nakata et al (2009) reported that UV-320, -326, -327, and -328 were accumulated in birds, fish and many invertebrates, as well as in sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant concentrations of some of these seven BUVSs have been found in different marine organisms like fish [25] lugworms, oysters, clams, crabs, ducks, sharks [15], and even in birds and mammals [24,26]. The presence of some BUVSs has also been reported in sediments samples [15,27,28], sewage sludges [29], wastewater [28,30], and surface waters [28].…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that the most lipophilic compounds can be lost during the sample pretreatment due to adsorption on the glass flask [30]. Therefore, a 10 % (v/v) of methanol was added to avoid this loss.…”
Section: Extraction Processmentioning
confidence: 99%
“…Due to their high production volume and wide application, BUVSs have been frequently detected in various environmental matrices such as municipal waste water, sewage sludge, sediment, soil, and indoor dust (Lai et al, 2014;Ramos et al, 2016;Wang et al, 2013a). Most BUVSs are detected in aquatic environments at mean concentrations ranging from 2.3 to 544.9 ng/L (Carpinteiro et al, 2010(Carpinteiro et al, , 2012García-Guerra et al, 2016;Kameda et al, 2011;Liu et al, 2011;Montesdeoca-Esponda et al, 2012;Song et al, 2014). Among these BUVSs, UV-326, UV-327, and UV-328 appear to be the most frequently detected compounds in environmental samples (Cantwell et al, 2015;Kameda et al, 2011;Langford et al, 2015;Liu et al, 2011;Nakata et al, 2009;Ruan et al, 2012;Song et al, 2014;Wick et al, 2016;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%